(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The consumption of ayahuasca for cultic purposes: public health order and religious freedom ABSTRACT: The article is inspired by the arguments contained in judgement no. 9897 of 2023 of the Council of State, which rejected the appeal against the inclusion of ayahuasca in the table of psychotropic substances. This narcotic is used in small quantities in the celebrations of the Churches of Daime, so the issue gains importance in identifying the conditions for the exercise of religious freedom and, in particular, freedom of worship. Since article 19 of the Constitution expressly refers only to good customs in religious rites as a limit to religious freedom, the paper will recognize, in the light of doctrine and courts’ judgements, some interpretative parameters aimed at promoting the balance between freedom of worship, right to health, the autonomy of the religious denomination in establishing liturgical principles and norms, the self- determination of individuals. SOMMARIO: 1. Le Chiese del Santo Daime: origini, credo e struttura - 2. Il Santo Daime in Italia e la vicenda processuale: l’inserimento dell’ayahuasca nella tabella I del T.U. sugli stupefacenti - 3. Il Consiglio di Stato e l’approccio salomonico nel contemperamento della libertà religiosa e del diritto alla salute - 4. Alcune osservazioni: la libertà religiosa tra diritto pubblico subiettivo e interesse legittimo e l’eterno ritorno della clausola di ordine pubblico.